Ciprofloxacin conjugated to diphenyltin(iv): a novel formulation with enhanced antimicrobial activity. Issue 33 (13th July 2020) - Chrysouli, M. P.; Banti, C. N.; Kourkoumelis, N.; Moushi, E. E.; Tasiopoulos, A. J.; Douvalis, A.; Papachristodoulou, C.; Hatzidimitriou, A. G.; Bakas, T.; Hadjikakou, S. K.
Abstract : The stereoisomer Δ- cis -[Ph2 Sn(CIP)2 ] (CIPTIN ) was obtained from ciprofloxacin and DPTC. CIPTIN exhibits stronger activity than that of ciprofloxacin against Gram positive or negative bacteria. Abstract : The metalloantibiotic of formula Ph2 Sn(CIP)2 (CIPTIN ) (HCIP = ciprofloxacin) was synthesized by reacting ciprofloxacin hydrochloride (HCIP·HCl ) (an antibiotic in clinical use) with diphenyltin dichloride (Ph2 SnCl2 DPTD ). The complex was characterized in the solid state by melting point, FT-IR, X-ray Powder Diffraction (XRPD) analysis, 119 Sn Mössbauer spectroscopy, X-ray Fluorescence (XRF) spectroscopy, and Thermogravimetry/Differential Thermal Analysis (TG-DTA) and in solution by UV-Vis, 1 H NMR spectroscopic techniques and Electrospray Ionisation Mass Spectrometry (ESI-MS). The crystal structure of CIPTIN and its processor HCIP was also determined by X-ray crystallography. The antibacterial activity of CIPTIN, HCIP·HCl, HCIP and DPTD was evaluated against the bacterial species Pseudomonas aeruginosa ( P. aeruginosa ), Escherichia coli ( E. coli ), Staphylococcus aureus ( S. aureus ) and Staphylococcus epidermidis ( S. epidermidis ), by the means of Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Inhibition Zones (IZs). CIPTIN shows lower MIC values than those of HCIP·HCl (up to 4.2-fold), HCIP (up to 2.7-fold) or DPTD (>135-fold), towards the tested microbes. CIPTIN is classified into bactericidal agents according to MBC/MIC values. The developing IZs are 40.8 ± 1.5, 34.0 ± 0.8, 36.0 ± 1.1 and 42.7 ± 0.8 mm, respectively which classify the microbes P. aeruginosa, E. coli, S. aureus and S. epidermidis to susceptible ones to CIPTIN . These IZs are greater than the corresponding ones of HCIP·HCl by 1.1 to 1.5-fold against both the tested Gram negative and Gram positive bacteria. CIPTIN eradicates the biofilm of P. aeruginosa and S. aureus more efficiently than HCIP·HCl and HCIP . The in vitro toxicity and genotoxicity of CIPTIN were tested against human skin keratinocyte cells (HaCaT) (IC50 = 2.33 μM). CIPTIN exhibits 2 to 9-fold lower MIC values than its IC50 against HaCaT, while its genotoxic effect determined by micronucleus assay is equivalent to the corresponding ones of HCIP·HCl or HCIP .